Atmospheric Deposition Effects on Plankton Communities in the Eastern Mediterranean: A Mesocosm Experimental Approach - Tsagaraki, Tatiana M.; Herut, Barak; Rahav, Eyal; Berman Frank, Ilana R.; Tsiola, Anastasia; Tsapakis, Manolis; Giannakourou, Antonia; Gogou, Alexandra; Panagiotopoulos, Christos; Violaki, Kalliopi; Psarra, Stella; Lagaria, Anna; et al. (Frontiers in Marine Science, 2017)
The effects of atmospheric deposition on plankton community structure were examined during a mesocosm experiment using water from the Cretan Sea (Eastern Mediterranean), an area with a high frequency of atmospheric aerosol deposition events. The experiment was carried out under spring-summer conditions (May 2012). The main objective was to study the changes induced from a single deposition event, on the autotrophic and heterotrophic surface microbial populations, from viruses to zooplankton. To this end, the effects of Saharan dust addition were compared to the effects of mixed aerosol deposition on the plankton community over 9 days. The effects of the dust addition seemed to propagate throughout the food-web, with changes observed in nearly all of the measured parameters up to copepods. The dust input stimulated increased productivity, both bacterial and primary. Picoplankton, both autotrophic and heterotrophic capitalized on the changes in nutrient availability and microzooplankton abundance also increased due to increased availability of prey. Five days after the simulated deposition, copepods also responded, with an increase in egg production. The results suggest that nutrients were transported up the food web through autotrophs that were favored by the Nitrogen supplied through both treatments. Although the effects of individual events are generally short lived, increased deposition frequency and magnitude of events is expected in the area, due to predicted reduction in rainfall and increase in temperature, which can lead to more persistent changes in plankton community structure. Here we demonstrate how a single dust deposition event leads to enhancement of phytoplankton and microzooplankton and can eventually, through copepods, transport more nutrients up the food web in the Eastern Mediterranean Sea.